Finite element analysis of 6 large PMMA skull reconstructions: A multi-criteria evaluation approach - Ridwan-Pramana, Angela; Marcián, Petr; Borák, Libor; Narra, Nathaniel; Forouzanfar, Tymour; Wolff, Jan (PloS one, 2017)
In this study 6 pre-operative designs for PMMA based reconstructions of cranial defects were evaluated for their mechanical robustness using finite element modeling. Clinical experience and engineering principles were employed to create multiple plan options, which were subsequently computationally analyzed for mechanically relevant parameters under 50N loads: stress, strain and deformation in various components of the assembly. The factors assessed were: defect size, location and shape. The major variable in the cranioplasty assembly design was the arrangement of the fixation plates. An additional study variable introduced was the location of the 50N load within the implant area. It was found that in smaller defects, it was simpler to design a symmetric distribution of plates and under limited variability in load location it was possible to design an optimal for expected loads. However, for very large defects with complex shapes, the variability in the load locations introduces complications to the intuitive design of the optimal assembly. The study shows that it can be beneficial to incorporate multi design computational analyses to decide upon the most optimal plan for a clinical case.
Keywords: Plastic Surgery Procedures; Tomography, X-Ray Computed; polymethylmethakrylát; Finite Element Analysis; lidé; Titanium; zákroky plastické chirurgie; Algorithms; titan; mechanický stres; Skull; Stress, Mechanical; předoperační období; Bone Plates; kostní destičky; Preoperative Period; Polymethyl Methacrylate; algoritmy; anatomické modely; počítačová rentgenová tomografie; analýza metodou konečných prvků; lebka; Models, Anatomic; Humans